Tobacco and cancer: epidemiology and new perspectives of prevention and monitoring in Mexico - Luz Myriam Reynales-Shigematsu (Instituto Nacional de Salud Pública, 2016)
Tobacco smoking is causal risk factor of at least 16 different types of cancer. In Mexico, smoking causes 6 035 premature deaths annually of lung cancer and 5 154 from other types. Additionally, 16 408 new smoking- attributable cases are diagnosed, causing high costs in the Mexican health sector. The WHO Framework Convention on Tobacco Control is the global strategy to reduce morbidity and mortality caused by this risk factor. Four more cost-effective strategies to ensure the population benefit are: i) increase tobacco taxes, ii) create 100% smoke-free environments, iii) warn damage through health warnings with pictograms and iv) total ban of advertising and promotion. Mexico is call upon to implement with determination this comprehensive strategy to reduce cancer mortality and assuring the health population. DOI: http://dx.doi.org/10.21149/spm.v58i2.7794